Challenges of Whale Watching and Swim With Dolphins in Mexico - Jorge Urbán, R.; Viloria-Gómora, Lorena (Frontiers in Marine Science, 2021)
Mexico is one of the top 10 whale-watching destinations in the world. The target species for “whale watching” (WW) are the gray whale, blue whale, humpback whale, and fin whale; the target species for “swim with dolphins” (SWD) are the bottlenose dolphin, spotted dolphin, spinner dolphin, and killer whale. WW has an increment of 666% income, 94% of trips, and 51% in the jobs generated in the last 11 years. Although Mexican legislation to regulate WW appears to be well designed, the great challenge is applying this normative in the field. In particular, it has been observed that surveillance and enforcement of normative differ significantly whether WW has carried out within a Marine Protected Area (MPA) or area without such designation. WW of gray and blue whales in El Vizcaíno Biosphere Reserve and Bahía de Loreto National Park, respectively, is developed within the MPAs. They are considered examples of acceptable WW practices. In contrast, in places without protected status as Puerto Vallarta, Jal., and Los Cabos, Baja California Sur (BCS), the WW practices have different problems related to boats’ presence without permission as sport fishing boats, private boats, and jet skis that do not respect WW guidelines. On the other hand, creating normativity or policies to regulate SWD in Mexico represents a current challenge. It is also a challenge to promote that local communities are involved in carrying out WW and SWD and are included in granting permits and the jobs and benefits of the economic spillover that these tourist activities generate.